Determinan Tingkat Pengangguran Terbuka di Provinsi Banten: Bukti Jobless Growth dan Ketidaksesuaian Struktural (2014–2024) - Nadia Solihah Fatimatuzzahro; Kikin Windhani (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study analyzes the determinants of the open unemployment rate (TPT) in Banten Province for the 2014–2024 period using panel data from eight regencies/cities. The estimation method used is the Fixed Effect Model (FEM) after conducting the Chow and Hausman tests to determine the most appropriate model. The variables analyzed include the Regency/City Minimum Wage (UMK), Gross Regional Domestic Product (GRDP), Human Development Index (HDI), government expenditure, and population. The results show that GRDP has a positive and significant effect on the TPT, indicating the phenomenon of jobless growth. Meanwhile, government expenditure and population have a negative and significant effect on the TPT. The UMK and HDI have no significant effect. These findings confirm that economic growth in Banten is not yet inclusive and has not optimally absorbed the workforce. The policy implications emphasize strengthening labor-intensive sectors, improving the quality and skills matching of the workforce, and optimizing government expenditure that promotes labor absorption.